A study on associated risks of smoking, alcohol and smokeless tobacco on hypertension among advocates - Edward, Shanthi; Periasamy, Praveena (International Journal Of Community Medicine And Public Health, 2019)
Background: Advocates, being stressed out and depressed in the law profession due to unstable work pattern, work overload and lack in coping up skills. They thrive a lot to survive in the profession. In such circumstances, lawyers may lean on alcohol or tobacco. In view of above issues, one of the main objectives of the study is to evaluate the association between use of alcohol, tobacco, smoking and hypertension among practising advocates. Methods: A cross-sectional study was conducted in a sample of 300 practising advocates at Madurai district court for a period of 1 year by simple random sampling method. Data was collected using structured interview schedule and analysed using SPSS. Results: Around 263 (87.66%) study participants were non-smokers and 37 (12.33%) were tobacco smokers. Among the tobacco smokers, a majority of 24 (64.86%) were found to be hypertensives (p=0.002). In the current study among the alcohol consumers, a majority of 26 (55.32%) were hypertensives and among the non-consumers of alcohol, only 38.34% were hypertensives (p=0.044). Conclusions: Advocates being professionals are well educated, informative and aware of complications. Adoption of healthy life style practices, the prevalence of hypertension may be reduced among the advocate community. Life style modifications such as cessation of smoking, alcohol and tobacco should be adopted. Promotive activities like arrangement of health camps in the court, health education, counselling on self-care, stress bursting leisure time activities would reduce the dependency on tobacco and alcohol.